Contesting citizenship in Latin America: The rise of indigenous movements and the postliberal challenge - Yashar, Deborah J (Cambridge University, 2013)
Deborah Yashar explains the contemporary and uneven emergence of Latin American indigenous movements - addressing both why indigenous identities have become politically salient in the contemporary period & why they have translated into significant political organizations in some places and not others.